2019
DOI: 10.1080/09537287.2019.1631459
|View full text |Cite
|
Sign up to set email alerts
|

Cloud platforms for remote monitoring system: a comparative case study

Abstract: Currently, industrial companies are increasingly introducing services to extend their tangible products. Remote monitoring solutions are one of the most implemented services by machine builders to manage their relationship with customers and also improve their business performance in the digital manufacturing era. However, the conventional method of remote monitoring cannot fulfil distributed business environments. Therefore, new solutions are needed to enable remote connection in manufacturing. By reviewing r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…e remote surveillance system receives, processes, and stores the data collected by the drone. Furthermore, the center of the grounds includes deep learning-based detection and alert activation capabilities [29]. At the ground monitoring console, the employees can view the acquired forest photos in real-time.…”
Section: Remote Monitoring Systemmentioning
confidence: 99%
“…e remote surveillance system receives, processes, and stores the data collected by the drone. Furthermore, the center of the grounds includes deep learning-based detection and alert activation capabilities [29]. At the ground monitoring console, the employees can view the acquired forest photos in real-time.…”
Section: Remote Monitoring Systemmentioning
confidence: 99%
“…In this way, the system contributes to an efficient performance measurement by its connection to the cloud [44]. Studies have reported that these applications have brought competitive advantages through technologies from Industry 4.0 supported by data‐based KPIs [63]. This combination of IIoT and the Cloud is fundamental for the digital transformation of data for performance measurement in manufacturing management [25, 57].…”
Section: Analysis Of Resultsmentioning
confidence: 99%
“…In this way, the system contributes to an efficient performance measurement by its connection to the cloud [44]. Studies have reported that these applications have brought competitive advantages through technologies from Industry 4.0 supported by data-based KPIs [63]. This combination of IIoT and the Cloud is fundamental for the digital transformation of data for performance measurement in manufacturing management [25,57] The reports observed in the research on how performance measurement is being treated in the context of Industry 4.0 identified that small and medium industries are constituted by systems with low adoption of technologies, consisting of legacy systems (machines and equipment), which do not have minimal connectivity capability with Industry 4.0 technologies.…”
Section: Model For Measuring Equipment Performancementioning
confidence: 99%
“…A number of literatures indicate that managing the integration of operating systems and servers can make a significant contribution to operational efficiency and system response speed [33]. By understanding the close relationship between OS and Server, companies can optimize the performance of their systems, reduce application deployment time, and increase response capacity to rapidly changing business demands [34].…”
Section: Iaic Transactions On Sustainable Digital Innovation (Itsdi)mentioning
confidence: 99%